DEVELOPMENT OF INNOVATION PUBLICATION OF PEDAGOG ON THE BASIS OF CRATIVE LIGHTING (International Educators Conference, 2025)
The article scientifically highlights the development of the innovative ability of the educator based on a creative approach. The article also provides scientific evidence that the ongoing reforms in the field of general secondary education, the development of the innovative capacity of the educator on the basis of a creative approach, are one of the main tasks set for educators.